PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL VALUE CLARIFICATION TECHNIQUE (VCT) BERBANTUAN MEDIA SPARKOL VIDIO SCRIBE DIKELAS V SDN 05 BIRUGO KOTA BUKITTINGGI - Putri, Firda Alya; Hamimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the low learning outcomes of students, especially in attitudes and knowledge in Pancasila Education learning. This is because teachers have not used innovative learning models that can attract students' attention. The purpose of this study is to describe the improvement in learning outcomes of students using the VCT model with the assistance of Sparkol Video Scribe media in class V SDN 05 Birugo, KotaBukiittinggi.This research is a classroom action research (PTK) using a qualitative approach and a quantitative approach to class V students. The research was carried out in two cycles consisting of the planning, implementation, observation and reflection stages. The subjects of the study were teachers and students in class V SDN 05 Birugo, Kota Bukittingi, totaling 25 people. The research data were obtained from the assessment of teaching modules, the implementation process and learning outcomes. The data collection techniques used were observation, tests and non-tests.The results of the study showed an increase as evidenced by the results of the analysis: a) In the aspect of the teaching module, cycle I obtained an average of 85.41% with good qualifications (B), increasing in cycle II to 95.83% with very good qualifications (SB), b) Implementation of learning in the teacher aspect, cycle I obtained an average of 79.68% with good qualifications (B), increasing in cycle 2 to 96.83% with very good qualifications (SB) and in the aspect of students, cycle I obtained an average of 79.68% with good qualifications (B) and increased in cycle II to 96.87% with very good qualifications (SB), c) Learning outcomes of students in cycle I in the attitude aspect obtained an average of 70.52 with sufficient qualifications (C) and increased in cycle II to 90 with good qualifications (B). Learning outcomes in the knowledge and skills aspect in cycle I obtained an average of 73.84% with sufficient qualifications (C) increasing in cycle II to 87.16% with good qualifications (B). Based on these results, it can be concluded that the pilot VCT model assisted by Sparkol Video Scribe media can improve student learning outcomes in Pancasila education lessons in class V of SDN 05 Birugo, Bukittinggi City.